PENERAPAN KURIKULUM 2013 : (STUDI KASUS PELAKSANAAN REMEDIASI MATA PELAJARAN IPA KELAS VII DI SALAH SATU MTs NEGERI SUNGAI KAKAP) - Herwinda, Herwinda; Sutrisno, Leo; S, Haratua Tiur Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the implementation of remedial programme that is performed by the teachers based on Permendikbud No. 81 A in the year of 2013 about the implementation of curriculum. The sample of this research was MTs Negeri Sungai Kakap. The tool of data collection was questionnaire which was given to the headmaster, teachers, and students. The other tools of data collection used were a list of inteview administered to the teachers and  the student score of evaluation test. The exact teachers in MTs Negeri Sungai Kakap have performed the remedial programme. The way of the remediation was revising students’ score which have not fulfil the school passing grade after evaluation  test or final year of the best. Based on the result, it was found that 55,1 % students admitted that the teacher did the remediation. Then 88,6 % students said that the way the teachers did the remediation. Was appropriatefor them. However, the implementation of remediation performed by the teachers in MTs Negeri Sungai Kakap has not been proper based on Permendikbud No.81 A in the year 2013 about the implementation of the curriculum. This research is expected to be used as a reference in implementation the remedial programme based on Permendikbud No.81 A in the year 2013. Keywords : Case study, The implementation, Remedial Programme, 2013 Curriculum, Saint Lesson